Recurrence of metastatic Merkel carcinoma after cessation of avelumab in a patient previously with a complete response - Alexandra Picard‐Gauci; Laura Troin; Madleen Chassang; Thierry Passeron; Henri Montaudié (JEADV Clinical Practice, 2022)
Abstract Background Merkel cell carcinoma (MCC) is a rare and aggressive cutaneous neuroendocrine malignancy. Immune checkpoint inhibitors (ICIs) have transformed the treatment landscape for patients with metastatic MCC (mMCC). In mMCC, the response duration after cessation of ICIs treatment for complete response (CR) is unknown. Observation We report a case of a woman in her 70s with metastatic MCC treated in first‐line with avelumab. The treatment was stopped after 2 years of CR. The patient relapsed after 11 months of cessation of treatment and rechallenge with avelumab at the same dosing regimen was decided. The first tumour assessment at 3 months after reintroduction revealed a CR. Discussion In contrast with observations made for patients who have discontinued ICIs in the metastatic melanoma setting, disease progression is observed after ICIs cessation in mMCC including for patients with low tumour burden and who achieve a CR. Conclusion The case of our patient underlines this risk of relapse and suggests great caution before stopping ICIs in patients treated for mMCC, even when they are in CR.